CRIMINAL LAW ON UNDERAGE CHILDREN DOING NARCOTICS BUSINESS WITH EVIL CONSENT - Ardi Rian Pratama; Tami Rusli; Suta Ramadhan (Universitas Labuhanbatu, 2023)
The involvement of children in the criminal justice process has the potential to cause various complex negative impacts. The intervention of juvenile criminal law, especially in the abuse of narcotics by children, has led children to various physical and psychological suffering. The purpose of child protection according to law is to guarantee the fulfillment of children's rights so that they can live, grow and participate optimally in human dignity and dignity, and receive protection from violence and discrimination, for the realization of quality Indonesian children, with noble character and prosperity. In article 59 of the Child Protection Act, it is stated that special protection must be given to children who conflict with the law. Article 64 paragraphs I and 2 state that children who conflict with the law are children who are in conflict with the law and are victims of crime.Keywords: Minors, Narcotics Business, Evil Conspiracy